TA’LÎL AL-AHKÂM DARI MASA RASULULLAH HINGGA MASA ULAMA USHÛL - Nur Lailatul Musyafaah (Prodi Hukum Pidana Islam Fakultas Syari’ah dan Hukum Universitas Islam Negeri Sunan Ampel Surabaya, 2016)
Abstract: Ta’lîl al-ahkâm is explaining by finding the legal reason. At the time of the Prophet, ta’lîl was contained in the Qur’an and hadith, among them: 1.’ Illat was embodied with the character of law, 2. Stating the legal position with its reason and historical background, 3. Explaining command accompanied by tafdhîl, 4. Explaining law with its reason marked with the letter of ta’lîl, 5. Explaining law and its explanation about the benefit or in otherwise. The methods of ta’lîl al-ahkâm at the time of companion: 1. Elimination of the penalty for refusing mafsadah, 2. Law is changed because its legal reason has been lost. 3. Not carrying out the command of Allah and His Messenger for the reason of mafsadah if the work is still performed, 4. Assigning the unassigned law at the time of Prophet for the sake of refusing mafsadah, 5. Doing something which was not done at the time of the Prophet for the reason of gaining benefit, 6. Establishing law based on the text without searching the illah. The methods of ta’lîl al-ahkâm at the period of tâbi’în and tâbi’ tâbi’în: 1. Advancing benefit, the law contained in the textis absolute or contrary to the public welfare, 2. Using the method of maslahah mursalah. 3. Leaving a permissible act by the reason of mafsadah. The methods of ta’lîl al-ahkâm in the period of Muslim scholars of ushûl: with text, ijmâ’, and al-sabr wa al-taqsîm.Keywords: Ta’lîl al-ahkâm, period of the Messenger, period of the Muslim scholars of ushûl. Abstrak: Ta’lîl al-ahkâm adalah menjelaskan dan cara menemukan ilat hukum. Pada masa Rasulullah, ta’lîl terdapat pada al-Qur’an dan hadis, di antaranya; 1. Ilat menyatu dengan sifat hukum, 2. Menyebutkan hukum beserta sebabnya. 3. Menjelaskan perintah diiringi dengan lafadz tafdhîl, 4. Menjelaskan hukum beserta ilatnya yang ditandai dengan huruf ta’lîl, 5. Menjelaskan hukum disertai dengan penjelasan maslahatnya, atau sebaliknya. Metode ta’lîl al-ahkâm pada masa Sahabat: 1. Meniadakan hukuman karena alasan menolak mafsadah, 2. Hukum menjadi berubah, karena ilatnya telah hilang, 3. Tidak melaksanakan perintah Allah dan RasulNya, karena adanya mafsadah apabila pekerjaan tersebut tetap dilaksanakan. 4. Menetapkan hukum yang belum ditetapkan Rasulullah demi menolak mafsadah, 5. Mengerjakan pekerjaan yang tidak dikerjakan pada masa Rasulullah, dengan alasan kebaikan, 6. Menetapkan hukum berdasarkan nas yang ada tanpa mencari ilat hukum.Metode ta’lîl al-ahkâm pada masa Tâbi’în dan Tâbi’ Tâbi’în: 1. Mendahuluan maslahat, jika hukum yang terkandung dalam nas bersifat mutlak atau umum bertentangan dengan kemaslahatan, 2. Menggunakan metode maslahah mursalah. 3. Meninggalkan pekerjaan yang mubah atau sunnah, karena jika dikerjakan akan mendatangkan mafsadah. Metode ta’lîl al-ahkâm pada Masa Ulama Ushûl: Dengan nash, ijma’, dan al-sabr wa al-taqsîm.Kata Kunci: Ta’lîl al-ahkâm, Masa Rasulullah, masa Ulama Ushûl.